The quadratic formula states that the solutions x1 and x2 of a quadratic function in the form y = ax^2 + bx + c is equal to:
![\begin{gathered} x_1=\frac{-b+\sqrt[]{b^2-4ac}}{2a} \\ x_2=\frac{-b-\sqrt[]{b^2-4ac}}{2a} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/91s05vl73299b9tb19a5xz2dthh9iqr776.png)
So, using this formula with the values a = 3, b = 4 and c = 2, we have that:
![\begin{gathered} x_1=\frac{-4+\sqrt[]{4^2-4\cdot3\cdot2}}{2\cdot3}=\frac{-4+\sqrt[]{16-24}}{6}=\frac{-4+\sqrt[]{-8}}{6} \\ x_1=\frac{-4+\sqrt[]{2^2\cdot(-2)}}{6}=\frac{-4+2\cdot\sqrt[]{-2}}{6}=\frac{-2+\sqrt[]{-2}}{3}=-(2)/(3)+i\cdot\frac{\sqrt[]{2}}{3} \\ x_2=\frac{-4-\sqrt[]{-8}}{6}=\frac{-2-\sqrt[]{-2}}{3}=-(2)/(3)-i\cdot\frac{\sqrt[]{2}}{3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o49c2zprv3x9x2c4xlb2xh0u5wup21r1fh.png)
Since the zeros have a complex part, the solutions are imaginary.